What’s happening in the kitchen? The influence of nutritional knowledge, attitudes and, practices (KAP), and kitchen characteristics on women’s dietary quality in Ethiopia - Temesgen Awoke Yalew; Masresha Tessema; Edward Lahiff (BMC Nutrition)
Abstract Background Low dietary quality significantly contributes to public health risks in low-income countries. This situation is particularly concerning for vulnerable groups, such as women and children, who are at increased risk of malnutrition due to inadequate access to proper nutrition. This study aimed to assess the influence of nutrition-related knowledge, attitudes, and practices, and kitchen characteristics on women’s dietary quality in Ethiopia. Method A population-based cross-sectional survey was conducted from August to September 2022 in five regions and two city administrations in Ethiopia. A multistage stratified cluster sampling method was employed. From ninety-nine enumeration areas, twenty eligible households were selected. A total of 1,980 women aged 15–49 years were included in this survey. The data were collected using a structured questionnaire about socio-demographic characteristics, food frequency, 24-hour dietary recall, and nutrition-related knowledge, attitudes, and practices. The determinants of dietary quality were identified using Poisson, logistic, and ordinary least square regression analyses. Variables with a p-value less than 0.05 were considered to indicate statistical significance. Results The results showed that the average dietary diversity score for women was 3.4 ± 0.85. Only 21.5% of the participants achieved the minimum dietary diversity for women (MDD-W), and the mean adequacy ratio for nutrients was 61.6%. The participants’ average nutrition-related knowledge, attitudes, and practices scores were 63%, 39%, and 23%, respectively. The regression analysis showed knowledge and attitude positively associated with dietary diversity and the mean nutrient adequacy ratio (P < 0.01). Cooking time and propensity to prepare new food were also positively associated with dietary diversity and with minimum dietary diversity (P < 0.01). Conclusion Our study showed that good nutrition-related knowledge and a positive attitude toward nutrition positively and significantly influence dietary quality, along with cooking time and the propensity to prepare new foods.